Decomposition and estimation of gauge transformation for Chern-Simons-Antoniadis-Savvidy forms - Suhaivi Hamdan; Erwin Amiruddin (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2022)
Cartan's extended homotopy formula is set to obtain the Chern-Simons-Antoniadis-Savvidy (ChSAS) measurement form transformation. This indicates a change in each of the results that the quasi-invariance nature of the gauge with a closed shape under the meter transformation. The results of the initial calculation of the ChSAS form then show a singlet anomaly for each value of n as a dimension variation. These results have illustrated the relationship with the Chern-Simon form theory. The results of the final calculation of the ChSAS shape on the gauge transformation are then described in relation to the Zumino anomaly which reaches an anomaly variation that depends on the p and n terms.